Left ventricular functions and mass of the adolescents and young adults with thalassemia major: An echocardiography study - Muhammad Ali; Sukman Tulus Putra; Djajadiman Gatot; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2006)
Background Thalassemia major (TM) is a transfusion-depen-dent disease. Multiple transfusions cause an accumulation of ironin the body. On the heart, iron can induce cardiomyopathy, theleading cause of death in TM.Objective To evaluate left ventricular functions and mass amongadolescents and young adults with TM.Methods A cross-sectional study was conducted on 58 patientswith TM in Cipto Mangunkusumo Hospital, Jakarta. Hematologicaldata was collected from medical record. Left ventricular systolic func-tions (EF, FS), diastolic functions (A, E, E/A ratio, IVRT), and mass(LVDDi, LVDSi, LVMi) were detected using an echocardiographySonos 4500. T test, linier regression, and multiple regression analy-sis were performed.Results Out of 32 TM patients, 30 were enrolled to study. Leftventricular systolic and diastolic functions of TM patients were lowerthan those of the control and statistically significant [EF 66.1% (SD4.9) and 71.6% (SD 5.6); P<0.0001, FS 36.0% (SD 3.7) and 39.8%(SD 5.5); P=0.003, E/A 2.14 (SD 0.4) and 1.83 (SD 0.3); P=0.002,respectively]. Left ventricular mass of TM patients was greater thanthat of control, and also statistically significant [LVMi 111.1 g/m 2(SD 30.8) and 75.4 g/m 2 (SD 14.5); P<0.0001, respectively]. Linierand multiple regression analysis showed significant and powerfulcorrelation between left ventricular diastolic functions (E/A ratio)and serum ferritin concentration (r=0.71; P<0.0001).Conclusion Left ventricular functions and mass of adolescentsand young adults with TM show abnormalities. The higher the con-centration of ferritin serum is, the more likely for TM patient to suf-fer from diastolic abnormality